Mechanical Behavior of Various Orthodontic Retraction Springs - Setiawan, Rachman; Idris, Muhammad; Prakasa, Tito Dwi (Journal of Engineering and Technological Sciences, 2011)
Retraction  spring  is  a  type  of  orthodontic  apparatus  that  is  used  to move a tooth with respect to another by utilizing its spring back effect. It is made of  metallic  wire  formed  to  individual  orthodontic  cases.  A  specific  geometry results in a set of force system, consisting of forces and moments, that provides specific movement effect when it is pre-activated to the adjacent teeth. Currently, orthodontists select its geometry depending on their knowledge and experience. It  is  based  on  separate  and  less-than-comprehensive  literatures  that  not  all orthodontists have access to. It may result in inaccuracies in treating individual tooth  retraction  case.  Engineering  approach  to  estimating  retraction  spring structural  behavior  is  proposed  through  analytical,  numerical  and  empirical methods.  Castigliano  method  is  used  as  the  analytical  approach,  whilst  finite element  method  is  used  as  the  numerical  approach.  The  two  simulation approaches  were  compared  to  the  experiments  to  obtain  the  best  simulation model.  The  behavior  of  the  simulation  models  agree  well  with  those  of experiments. Hence, the simulation models were used to simulate a large number of  geometries  to  form  database  of  structural  behavior  of  retraction  spring  that could be used in the geometry selection by orthodontists.